Real Country : Music and Language in Working-Class Culture - Fox, Aaron A., 1964- (Book collections on Project MUSE., 2004)
In Lockhart, Texas, a rural working-class town just south of Austin, country music is a way of life. Conversation slips easily into song, and the songs are full of conversation. Anthropologist and musician Aaron A. Fox spent years in Lockhart making research notes, music, and friends. In Real Country, he provides an intimate, in-depth ethnography of the community and its music. Showing that country music is deeply embedded in the textures of working-class life, Fox argues that it is the cultural and intellectual property of working-class people and not only of the Nashville-based music industry or the stars whose lives figure so prominently in popular and scholarly writing about the genre. Fox spent hundreds of hours observing, recording, and participating in talk and music-making in homes, beer joints, and garage jam sessions. He renders the everyday life of Lockhart & rsquo;s working-class community in detail, right down to the ice cold beer, the battered guitars, and the technical skills of such local musical legends as Randy Meyer and Larry & ldquo;Hoppy & rdquo; Hopkins. Throughout, Fox focuses on the human voice. His analyses of conversations, interviews, songs, and vocal techniques show how feeling and experience are expressed, and how local understandings of place, memory, musical aesthetics, working-class social history, race, and gender are shared. In Real Country, working-class Texans re-imagine their past and give voice to the struggles and satisfactions of their lives in the present through music.